Cybersecurity crimes in cryptocurrency exchanges (2009–2024) and emerging quantum threats: the largest unified dataset of CEX and DEX incidents - Olushola, Akinlemi; Meenakshi, S. P. (Frontiers in Blockchain, 2025)
Cryptocurrency exchanges are integral to the digital asset economy; however, their rapid growth has been accompanied by recurrent high-impact cyberattacks that erode trust and inflict substantial losses. Guided by the PRISMA-ScR framework, this review systematically screened peer-reviewed and industry sources to construct a validated dataset of 220 major incidents (2009–2024) across centralized (CEX) and decentralized (DEX) exchanges. We classify attack vectors, analyze repeated high-impact patterns, and identify systemic vulnerabilities spanning cryptographic mechanisms and exchange infrastructure. Across CEX platforms, four of ten identified attack types accounted for 62 of the 80 incidents and approximately $1.764 billion in losses (42.1% of the $4.191 billion CEX total). Across DEX platforms, five of eighteen attack types were responsible for 120 of 140 incidents, totaling $3.755 billion (87.3% of the $4.303 billion DEX total). The overall losses sum to $8.494 billion across 220 incidents (80 CEX; 140 DEX). Repeated vectors comprised 182/220 incidents and $5.519 billion (65.0%) of losses, dominated by wallet/key compromise (78 incidents; $2.394 billion) and DEX system/server/protocol exploits (56 incidents; $1.939 billion); these two classes account for 134/182 repeated incidents (79.1%) and $4.333 billion (78.5%) of repeated losses. We examine the susceptibility of cryptographic defenses to emerging quantum adversaries and assess the exchange readiness for post-quantum threats. This study is the first to systematically compile and quantitatively analyze cybercrime incidents affecting both centralized and decentralized cryptocurrency exchanges in a unified dataset, enabling unprecedented comparability of systemic risks with actionable insights for cybersecurity researchers, regulators, and exchange operators seeking quantum-safe infrastructure evolution.